Treatment of Basal Cell Carcinoma: A Focus on the Role of Mohs Micrographic Surgery - Maguire, Ciara (Trinity Student Medical Journal, 2008)
Basal Cell Carcinoma (BCC) is the most common cancer in human and the leading cutaneous malignancy of the fair skinned Irish population. Mohs Micrographic Surgery is a specialised operational technique used in the treatment of BCC. It involves excision of the cancer and microscopic examination of 100% of the surgical margins. It has the highest cure rate of any treatment for BCC and the best cosmetic outcome as it does not sacrifice unnecessary surrounding tissue.